2004
DOI: 10.1038/sj.cdd.4401399
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast formation, survival and morphology are highly dependent on exogenous cholesterol/lipoproteins

Abstract: Osteoporosis is associated with both atherosclerosis and vascular calcification. No mechanism yet explains the parallel progression of these diseases. Here, we demonstrate that osteoclasts (OCL) depend on lipoproteins to modulate cellular cholesterol levels and that this controls OCL formation and survival. Removal of cholesterol in OCL via high-density lipoprotein or cyclodextrin treatment dose-dependently induced apoptosis, with actin disruption, nuclear condensation and caspase-3 activation. One mechanism l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
89
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 69 publications
6
89
1
1
Order By: Relevance
“…More recently, we found that during osteoclastogenesis, RANKL induces the expression of caveolin-1 (Cav-1) (40), a principal scaffolding protein of lipid rafts and caveolae. Furthermore, depletion of exogenous LDL causes impaired NFATc1 activation and consequently reduces osteoclast formation (40), consistent with other studies (29,30). These results suggest a tight correlation between osteoclast differentiation and cholesterol.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…More recently, we found that during osteoclastogenesis, RANKL induces the expression of caveolin-1 (Cav-1) (40), a principal scaffolding protein of lipid rafts and caveolae. Furthermore, depletion of exogenous LDL causes impaired NFATc1 activation and consequently reduces osteoclast formation (40), consistent with other studies (29,30). These results suggest a tight correlation between osteoclast differentiation and cholesterol.…”
supporting
confidence: 90%
“…Furthermore, an in vivo study has shown that a mouse strain with susceptibility to atherosclerosis (C57BL/6) loses a greater amount of bone mass in response to a high-fat diet than atherosclerosis-resistant strains (26). In addition, several in vitro studies have demonstrated that oxidized LDL (ox-LDL) inhibits osteoblast differentiation (27,28), whereas an absence of native LDL suppresses osteoclast formation in cocultures of spleen cells or bone marrow cells as osteoclast progenitors and osteoclast differentiation-supporting stromal or osteoblastic cells (29,30). Such coculture systems, however, could not provide a evidence for direct action of LDL on osteoclast precursors.…”
mentioning
confidence: 99%
“…In vitro and in vivo studies in rodents (Mundy et al, 1999;Grasser et al, 2003;Luegmayr et al, 2004) and epi-demiological studies (Bauer, 2003) have found that statins, inhibitors of HMG-CoA reductase, increase bone density especially in postmenopausal women (Edwards et al, 2000). While these studies are difficult to interpret in detail because of complexity and confounding factors inherent in epidemiological studies, our analysis suggests that cholesterol levels regulate osteoclastogenesis at multiple levels.…”
Section: Role Of Cholesterol In Osteoclast Developmentmentioning
confidence: 70%
“…Studies of this pathway have clarified how diverse physiological and pathophysiological signals exert their effects on osteoclast formation, function and survival, and ultimately control skeletal remodelling and bone mass. 2 Two papers 3,4 in the current issue of Cell Death and Differentiation further extend our understanding of osteoclast formation and survival. The paper by Yang et al 3 proposes a new role for decoy receptor 3 (DcR3) in regulating osteoclastogenic differentiation of haematopoietic precursor cells, whereas the paper by Luegmayr et al raises the possibility that osteoclast function and survival are regulated by exogenous cholesterol/lipoprotein levels.…”
mentioning
confidence: 95%
“…The paper by Luegmayr et al 4 provides evidence to suggest that osteoclast function and survival is highly dependent on exogenous sources of cholesterol. They show that cholesterol acceptors, including high-density lipoprotein, induce osteoclast apoptosis; that osteoclasts deficient in the low-density lipoprotein receptor (LDLR), in the presence of M-CSF and RANKL, undergo apoptotic cell death at an increased rate compared with wild-type osteoclasts; and that osteoclasts are highly sensitive to forced cholesterol removal because of the absence of an endogenous cholesterol biosynthesis feedback response.…”
mentioning
confidence: 99%